Interrelation between soil compaction and field performances of different machinery at MADA’s rice field, Kedah, Malaysia - Mat Nasir, Radiah (2021)
Operation of machinery on the field are causing damage that are clearly observed at the top soil level. However, because the Muda Agricultural Development Authority (MADA) region is spatially dispersed, assessing the extent and level of damaged soil layer is challenging. The study focused on affected soil under various machinery weight and size, for different soil conditions. In this study, a minimum of three plots with slightly different soil types were put under test using four different types of machinery; rubber-wheeled tractor (RWT); half-track tractor (HTT); mini combine harvester (CM); large combine harvester (CB). The field tests were replicated for two seasons of paddy plantation processes: tillage and harvesting. Before the test, soil field condition was analysed to determine the soil texture. Soil damage was measured by determining soil compaction quantified by bulk density (BD), soil penetration resistance (SR) and soil moisture (SM). Machinery performances were also evaluated in term of field efficiency (FE), effective field capacity (EFC), field capacity (FC) and field machine index (FMI). The damaged soil compaction was successfully quantified and compared for land preparation and harvesting in Kedah, Malaysia. In this study the value 0.4 - 0.5 MPa for tractor and 0.6 – 0.7 MPa for harvester at 0-20 cm depth concluded that RWT, HTT, CM and CB are the machines suitable for rice field operation. Based on machinery performance only significant on EFC but here is no significant difference between the HTT and RWT, and CM and CB in terms of FE, EFC and FMI. Lastly, map of BD, SM and PR were created entire plot by using Geostatics particularly Kriging interpolation method to develop maps using ArcGIS® software. This information can be used by the farmer in order to improve farm’s machinery management.